Seismic vulnerability of bhutanese vernacular stone masonry buildings: From damage observation to fragility analysis - Gautam, Dipendra (2022)
A moderate earthquake of local magnitude 6.4 occurred in Sonitpur Assam, India on April 28, 2021. Although the earthquake occurred in India, Bhutan suffered considerable damage to structures and infrastructures, especially in the eastern districts. Due to inherent vulnerabilities of Bhutanese residential buildings, encapsulated in rural stone masonry and rammed earth construction, widespread damages were reported in many districts although the shaking was moderate only. We report the damage mechanisms observed in buildings and infrastructures and juxtapose the mechanisms with seismic vulnerability of Bhutanese residential buildings using analytical and empirical approaches. Finite element analysis is performed to validate the failure mechanisms. Intensity map for the earthquake is constructed based on the damage description and vulnerability curve is derived for rural stone masonry building class using the damage data of 2009, 2011, and 2021 earthquakes. The sum of observations and analyses highlights that the Bhutanese residential buildings are likely to be damaged considerably even by moderate shaking, and their capacities are expected to be far exceeded by strong shaking.